2009
DOI: 10.3109/09638280903171592
|View full text |Cite
|
Sign up to set email alerts
|

Gait characteristics of children with hemiplegic cerebral palsy before and after modified constraint-induced movement therapy

Abstract: This investigation assessed selected gait parameters of children with hemiparesis before and after participation in a modified constraint-induced movement therapy program (mCIMT). Recent advances in the understanding of the relationship between mCIMT and cortical reorganization supports the use of upper-extremity mCIMT to treat lower extremity deficits. However, the effects of mCIMT on the gait patterns of children with hemiparesis remain unclear. Twelve preschool children participated in a mCIMT program for 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 36 publications
0
13
0
2
Order By: Relevance
“…11,15,40 With regard to the evaluation of upper limb kinematics, we evaluated reaching and hand-to-mouth movements. Overall, our results are in line with the literature, which reported a positive trend for the CIMT program on the QUEST scale 3 weeks after the treatment 14 in children after TBI; positive changes were also found in the CP children after CIMT, in terms of the QUEST, GMFM, and other clinical scales.…”
Section: Discussionmentioning
confidence: 99%
“…11,15,40 With regard to the evaluation of upper limb kinematics, we evaluated reaching and hand-to-mouth movements. Overall, our results are in line with the literature, which reported a positive trend for the CIMT program on the QUEST scale 3 weeks after the treatment 14 in children after TBI; positive changes were also found in the CP children after CIMT, in terms of the QUEST, GMFM, and other clinical scales.…”
Section: Discussionmentioning
confidence: 99%
“…Gross motor performance appears to be a relevant outcome measure for CIMT with infants. Other studies have demonstrated the effect of CIMT on gross motor performance in infants (Coker et al, 2009) and on gait patterns in preschool children (Coker, Karakostas, Dodds, & Hsiang, 2010). …”
Section: Discussionmentioning
confidence: 98%
“…A number of researchers have evaluated the effectiveness of balance training on stance and gait in children with hemiplegic CP, [19][20][21][22][23] but none has evaluated static balance in children with hemiplegic CP. Evaluation of standing balance under conditions with sensory conflicts would help estimate the ability in children with hemiplegic CP to resolve intersensory conflicts, thereby facilitating better interventions for improving balance and gross motor abilities.…”
Section: Introductionmentioning
confidence: 99%